Description of Gross Motor Development of Stunted Children Aged 3-5 Years in Gantarang District, Bulukumba Regency - Syam, Andi Tzamrah Istiqani; Hasbiah, Nurhikmawaty; Purnamasary, Nahdiah; Hamisah; Tiar Erawan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
The focus of the World Health Organization (WHO) on health problems related to children today is the problem of stunting. The high number of stunting in the world including Indonesia has made the government try to create a movement to minimize stunting in Indonesia because of the many negative effects stunting causes. One of them is gross motor development disorder. This study aims to describe the development of stunted children's gross motor skills in Gantarang District, Bulukumba Regency. The type of research used in this research is descriptive with a cross sectional approach. The population in this study were stunted children aged 3-5 years in Gantarang District, Bulukumba Regency, with a total sample of 120 children (n=120). Data collection was carried out by taking purposive sampling through the TGMD-2 questionnaire. The collected data was then processed in SPSS version 26 to see the distribution of respondents, parents of respondents and gross motor skills of respondents. The description of the development criteria for gross motor skills for stunting children aged 3-5 years is dominated by male sex (50.8%), age 3 years (50.7%), body weight > 2,500 grams (86.6%), height per age (TB /U) the highest criteria were short criteria (80.0%), weight for age (BB/U) the highest criteria were less criteria (53.3%) and height per body weight (BB/TB) the highest criteria were good nutrition criteria (85.0 %) and it was found that 36 children (30.0%) had above average gross motor skills and there was 1 child with low criteria (0.8%) and 2 children with very low criteria (1.7%). so that better attention is needed from the government, physiotherapists and parents for the development of stunted children's gross motor skills.